Composite building materials based on nanomodified cement systems - Natalia O. Kopanitsa; Olga V. Demyanenko; Anzhelika A. Kulikova; Alexander F. Buryanov; Nadezhda A. Lukyanova; Vadim G. Soloviev (Нанотехнологии в строительстве, 2023)
ABSTRACT: Introduction. This research work investigates the combined influence of nano-sized silicon dioxide (nano-SiO2 ), carbon nanotubes and surfactants on the structural and technological characteristics of cement compositions. Materials and research methods. The paper reveals the findings of a study on the effects of various dispersion techniques of carbon nanotubes (CNT) in surfactants, such as mechanical dispersion, ultrasonic treatment, and a combined method. It considers the uniformity of CNT distribution within the plasticizer and within the cement system, along with their impacts on the physical and mechanical properties of cement stone and concrete. Differential thermal and electron microscopic analysis of aqueous dispersions of carbon nanotubes and hardened activated nanomodified cement stone was carried out. Results and discussion. It has been experimentally proven that mixing nanotubes in dry cement does not allow them to be evenly distributed throughout the volume of the mixture. When using carbon nanotubes, the maximum effect is achieved when they are introduced into aqueous dispersions of plasticizers. The percentage of plasticizer was 1%, CNT 0,1% per 1 liter of water. The most effective method of dispersing carbon nanotubes in a plasticizer is a combined one. The results obtained were used in the preparation of cement stone and concrete compositions. Conclusion. The results show that complex additives consisting of nano-SiO2 and aqueous dispersions of carbon nanotubes have a positive effect on the physical-mechanical and structural-technological properties of cement stone and concrete. Graphic dependencies are shown indicating the effectiveness of using complex additives in the production of cement composites